NILAI SOSIAL DAN BUDAYA PADA NOVEL PANGGIL AKU KARTINI SAJA KARYA PRAMOEDYA ANANTA TOER - Fitri Novita Dewi; Mamluatun Ni’mah; Ahmad Ilzamul Hikam (Universitas Nahdlatul Ulama Sunan Giri, 2023)
“This study aims to discuss as a whole the social and cultural values contained in the novel Panggil Aku Kartini Saja by Pramoedya Ananta Toer. This study uses a qualitative descriptive method. This type of research is included in the realm of qualitative research. The approach in research uses a literary sociology approach that focuses on its study of socio-cultural values. Data collection techniques used in this research are reading techniques, note-taking techniques, and library techniques. Socio-cultural values contained in the novel Panggil Aku Kartini Saja, namely in the form of social values in the aspect of education, social values in accepting rights and obligations, lineage differences between nobles and commoners, traditions, customs, feelings of treatment, interactions between fathers and children and Kartini's art.”